Hadith #3013 - Sunan Abi Dawud - Bashayr bin al-Yasar al-Harithi al-Ansar بشير بن يسار مولى بني حارثة; Muhammad bin Mskyn bin Nmylh محمد بن مسكين بن نميلة; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Yahya bin Hsan يحيى بن حسان; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
Bashir bin Yasar said “When Allaah bestowed Khaibar on His Prophet (ﷺ) as fai’ (spoils), he divided it into thirty six lots. Each lot comprised one hundred portions. He separated its half for his emergent needs and whatever befalls him. Al Watih and Al Kutaibah and Al Salalim and whatever acquired with them. He separated the other half and he divided Al Shaqq and Nata’ and whatever acquired with them. The portion of the Apostle of Allaah(ﷺ) lay in the property acquired with them.
Grade: Sahih

Hadith #3043 - Sunan Abi Dawud - Bjalh bin Abd'h al-Tmymy al-Nbry بجالة بن عبدة; Da'ud bin Abi Hnd داود بن أبي هند; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; ibn Abbas; Muhammad bin Mskyn bin Nmylh محمد بن مسكين بن نميلة; Qshyr bin 'Amr قشير بن عمرو; Yahya bin Hsan يحيى بن حسان (Sunan Abi Dawud)
Amr ibn Aws and AbulSha’tha’ reported that Bujalah said: I was secretary to Jaz’ ibn Mu’awiyah, the uncle of Ahnaf ibn Qays. A letter came to us from Umar one year before his death, saying: Kill every magician, separate the relatives of prohibited degrees from the Magians, and forbid them to murmur (before eating). So we killed three magicians in one day, and separated from a Magian husband his wife of a prohibited degree according to the Book of Allah. He prepared abundant food and call
Grade: Sahih

Hadith #4628 - Sunan Abi Dawud - Muhammad bin Mskyn bin Nmylh محمد بن مسكين بن نميلة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) was alive, we used to say: The most excellent member of the community of the Prophet (ﷺ) after himself is Abu Bakr, then ‘Umar, then ‘Uthman.
Grade: Sahih